2019
DOI: 10.1111/jnc.14791
|View full text |Cite
|
Sign up to set email alerts
|

Hyaluronan synthesis supports glutamate transporter activity

Abstract: Hyaluronan is synthesized, secreted, and anchored by hyaluronan synthases (HAS) at the plasma membrane and comprises the backbone of perineuronal nets around neuronal soma and dendrites. However, the molecular targets of hyaluronan to regulate synaptic transmission in the central nervous system have not been fully identified. Here, we report that hyaluronan is a negative regulator of excitatory signals. At excitatory synapses, glutamate is removed by glutamate transporters to turn off the signal and prevent ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Astrocytes contribute to synaptic function in part by regulating glutamate uptake from the synaptic cleft, preventing glutamate-induced neurotoxicity [58,59]. Hyaluronan supports the activity of the glial glutamate transporter [60]. Thus, while our data supports a model in which HA is directly synthesized into the developing synaptic cleft, it is interesting to speculate that with further development, HA is synthesized by associated astrocytes, which would surround and stabilize mature synaptic contacts.…”
Section: Discussionmentioning
confidence: 50%
“…Astrocytes contribute to synaptic function in part by regulating glutamate uptake from the synaptic cleft, preventing glutamate-induced neurotoxicity [58,59]. Hyaluronan supports the activity of the glial glutamate transporter [60]. Thus, while our data supports a model in which HA is directly synthesized into the developing synaptic cleft, it is interesting to speculate that with further development, HA is synthesized by associated astrocytes, which would surround and stabilize mature synaptic contacts.…”
Section: Discussionmentioning
confidence: 50%
“…We found that the colocalization of the three proteins is significantly increased in BD (3-way ANOVA, p = 0.0188, Figure 7D), further supporting an upregulation of SPP1-CD44 signalling in BD astrocytes. In light of our transcriptomic and IHC results, this upregulated communication appreas to be implicated in BD and could be contributing to the downregulated immune responses in astrocytes 87 and dysfunctional glutamate homeostasis 88 .…”
Section: Resultsmentioning
confidence: 75%
“…By expressing both hyaluronidase and MMPs, astrocytes play an important role in hyaluronan synthesis and catabolism ( Muir et al, 2002 ; Al’Qteishat et al, 2006 ). HA in turn regulates the morphology of astrocytes and proper trafficking and function of glutamate transporters by CD44-evoked Rac1 signaling ( Hayashi et al, 2019 ; Peters and Sherman, 2020 ).…”
Section: Homeostatic Regulation Of Extracellular Matrix and Perineuro...mentioning
confidence: 99%